1990
DOI: 10.1139/z90-092
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral decisions made under the risk of predation: a review and prospectus

Abstract: Predation has long been implicated as a major selective force in the evolution of several morphological and behavioral characteristics of animals. The importance of predation during evolutionary time is clear, but growing evidence suggests that animals also have the ability to assess and behaviorally influence their risk of being preyed upon in ecological time (i.e., during their lifetime). We develop an abstraction of the predation process in which several components of predation risk are identified. A review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

132
5,767
19
41

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 6,967 publications
(5,959 citation statements)
references
References 257 publications
132
5,767
19
41
Order By: Relevance
“…Species evolved a variety of defense strategies to reduce their predation risk ranging from camouflage, apparent dead, mimicry, aposematism, warning calls, weaponry, chemical defense to escape behavior (Endler, 1991; Lima & Dill, 1990). These defense mechanisms interact in different ways with the predator.…”
Section: Introductionmentioning
confidence: 99%
“…Species evolved a variety of defense strategies to reduce their predation risk ranging from camouflage, apparent dead, mimicry, aposematism, warning calls, weaponry, chemical defense to escape behavior (Endler, 1991; Lima & Dill, 1990). These defense mechanisms interact in different ways with the predator.…”
Section: Introductionmentioning
confidence: 99%
“…Since the importance of detecting motion, especially approaching predators (Lima and Dill 1990), is paramount, and turbidity decreases the range at which visual signals can be detected, we hypothesize that guppies reared in turbid water increase the expression of long wavelength-sensitive opsins important in motion detection. Furthermore, previous studies have shown that fish placed in turbid water decrease activity (Leahy et al 2011;Borner et al 2015); thus, we predict that guppies reared in clear water and placed in turbid water will show decreases in activity, while fish reared in turbid water may be acclimated to turbid conditions (in part via transcriptional changes in their visual system) such that activity decrease in turbid water will not be observed.…”
Section: Introductionmentioning
confidence: 99%
“…A transition from freeze to flee was not described as spontaneous, but dependent on other factors such as approach of the predator. Certainly, it is impossible to freeze and flee simultaneously, and at any given moment a prey can execute only one of these defenses [29]. However, here we assumed that only freezing or only fleeing would make the prey predictable and vulnerable.…”
Section: Introductionmentioning
confidence: 99%